2019
DOI: 10.1080/15230430.2019.1605798
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate and thaw depth on alpine vegetation variations at different permafrost degrading stages in the Tibetan Plateau, China

Abstract: Understanding the driving forces for alpine vegetation variations at different permafrost degrading stages is important when the Tibetan Plateau is experiencing climate warming. We applied the modified Frost Number model to simulate frozen ground distributions in the Tibetan Plateau and calculated the maximum thawing depth by the Stefan approach. We classified the simulated frozen ground into three subzones: seasonal frozen ground zone, changing zone, and permafrost zone. We evaluated the effects of precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 76 publications
(106 reference statements)
0
8
0
Order By: Relevance
“…Groundwater sustains rivers in winter and buffers droughts to maintain fragile ecosystems, especially in arid or semi‐arid regions (de Graaf et al., 2019; Famiglietti, 2014; Fan et al., 2013; Gleeson et al., 2016; Rodell et al., 2009; Taylor et al., 2013; Yao et al., 2021). Over the past decades, TP has experienced dramatic glacier retreat, permafrost degradation, and lake expansions caused by global warming (Brun et al., 2017; Cheng & Wu, 2007; Feng et al., 2019; Ji et al., 2020; Kuang & Jiao, 2016; Yao et al., 2012, 2022; Yi et al., 2021; Zhang et al., 2020). The accelerated transformation from solid water into liquid water may alter groundwater recharge, storage, and discharge to varying degrees, resulting in substantial changes in the groundwater system (Cheng & Jin, 2013; Gao et al., 2018; Huss & Hock, 2018; Lin et al., 2020; Yin et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater sustains rivers in winter and buffers droughts to maintain fragile ecosystems, especially in arid or semi‐arid regions (de Graaf et al., 2019; Famiglietti, 2014; Fan et al., 2013; Gleeson et al., 2016; Rodell et al., 2009; Taylor et al., 2013; Yao et al., 2021). Over the past decades, TP has experienced dramatic glacier retreat, permafrost degradation, and lake expansions caused by global warming (Brun et al., 2017; Cheng & Wu, 2007; Feng et al., 2019; Ji et al., 2020; Kuang & Jiao, 2016; Yao et al., 2012, 2022; Yi et al., 2021; Zhang et al., 2020). The accelerated transformation from solid water into liquid water may alter groundwater recharge, storage, and discharge to varying degrees, resulting in substantial changes in the groundwater system (Cheng & Jin, 2013; Gao et al., 2018; Huss & Hock, 2018; Lin et al., 2020; Yin et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, several studies examined the influence of climate variability on vegetation variability represented by NDVI, EVI and above-ground biomass (Le Houerou et al 1988;Lotsch et al 2003;Vicente-Serrano et al 2013;Thornton et al 2014;Seddon et al 2016;Sloat et al 2018;Bao et al 2019;Chen et al 2019;Feng et al 2019a;Stanimirova et al 2019), and revealed the dominance of precipitation variability in the arid and semi-arid ecosystems. For example, using the CASA model, Bao et al (2019) showed that annual NPP was about 265 g C/m 2 on the Mongolian Plateau and that summer drought played a significant role in determining annual NPP variability.…”
Section: Introductionmentioning
confidence: 99%
“…However, similar studies on the TP are very limited. Only Feng et al (2019a) found that precipitation could account for the NDVI variability in the permafrost zone of the TP in some periods during 1982-2012.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings of the generic responses of frozen soil depth and vegetation production to variations of air temperature across the Tibetan Plateau are in accordance with the opinion that the warming is causing changes in cryosphere and biosphere, such as deepening of the permafrost active layer (Cheng & Wu, 2007; Lu et al, 2017), shrinking permafrost area (Guo et al, 2012), shortening freeze period of the seasonally frozen soils (Cuo et al, 2015; Luo et al, 2020; Zhao et al, 2004), and advance of greenness and increasing plant productivity (Feng et al, 2019; Shen et al, 2015; Zhang et al, 2014). The Tibetan Plateau is experiencing climate warming at a high increasing rate, which is accelerating ground warming and promoting the frozen soil thawing (Guo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%